1999
DOI: 10.1016/s0893-133x(99)00055-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Biochemical Manifestations of Mecamylamine-Precipitated Nicotine Withdrawal in the Rat Role of Nicotinic Receptors in the Ventral Tegmental Area

Abstract: Brain mesolimbic dopamine (DA) neurons are considered critical for the dependence-producing action of nicotine, and its stimulatory effect on behavior and DA neurotransmission appears largely mediated via nicotinic receptors (nAChRs) in the ventral tegmental area (VTA). The nAChR antagonist mecamylamine administered systemically in chronically nicotine-treated rats elicits a behavioral withdrawal syndrome concomitant with a reduced DA output in the nucleus accumbens (NAC). Here, we investigated the behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 75 publications
6
75
0
Order By: Relevance
“…As anticipated (Epping-Jordan et al 1998;Hildebrand et al 1997Hildebrand et al , 1999Malin et al 1992;Watkins et al 2000b), nicotine withdrawal also led to significant increases in somatic signs. Most importantly, the results indicated that the co-administration of fluoxetine, a selective serotonin reuptake inhibitor, and p-MPPI, a 5-HT 1A receptor antagonist, alleviated the diminished interest in rewarding stimuli observed during withdrawal from nicotine or amphetamine in rats.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…As anticipated (Epping-Jordan et al 1998;Hildebrand et al 1997Hildebrand et al , 1999Malin et al 1992;Watkins et al 2000b), nicotine withdrawal also led to significant increases in somatic signs. Most importantly, the results indicated that the co-administration of fluoxetine, a selective serotonin reuptake inhibitor, and p-MPPI, a 5-HT 1A receptor antagonist, alleviated the diminished interest in rewarding stimuli observed during withdrawal from nicotine or amphetamine in rats.…”
Section: Discussionsupporting
confidence: 59%
“…Further, considering the strong evidence implicating reduced serotonergic neurotransmission as one of the neurochemical abnormalities associated with depression (for reviews, see Caldecott-Hazard et al 1991;Caldecott-Hazard and Schneider 1992;Heninger et al 1996;Markou et al 1998;Meltzer and Lowy 1988;Willner 1985), it can be hypothesized that there is homology between the symptom of "diminished interest or pleasure" seen in individuals withdrawing from drugs of abuse and the same symptom seen in depressed patients. Decreased dopaminergic neurotransmission is another neurobiological abnormality common to withdrawal from a variety of drugs of abuse, including nicotine (Hildebrand et al 1999;Parsons et al 1995;Weiss et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, nicotine administration also modifies locomotion, anxiety, memory, nociception, and produces rewarding effects in several animal models (Clarke and Kumar, 1983;Hildebrand et al, 1999;Marubio et al, 1999;Picciotto et al, 1995). Neuroanatomical studies have shown a high density of CB1 receptors in neurons of the cerebellum, basal ganglia, limbic cortices, hippocampus, 3 hypothalamus and different nuclei of the extended amygdala (Tsou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%